2017
DOI: 10.1681/asn.2017040436
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation in Peritoneal Dialysis–Induced Arteriolopathy

Abstract: Cardiovascular disease (CVD) is the leading cause of increased mortality in patients with CKD and is further aggravated by peritoneal dialysis (PD). Children are devoid of preexisting CVD and provide unique insight into specific uremia- and PD-induced pathomechanisms of CVD. We obtained peritoneal specimens from children with stage 5 CKD at time of PD catheter insertion (CKD5 group), children with established PD (PD group), and age-matched nonuremic controls (=6/group). We microdissected omental arterioles fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…However, while systemic complement activation (the fluid phase) is similar between PD patients and patients with ESKD, higher intravascular complement depositions (solid phase) have been shown in children with PD compared to non-PD children with ESKD. Omental and parietal arterioles from PD patients demonstrated a higher presence of C1q, C3d, and C5b-9 ( 88 ).…”
Section: Peritoneal Dialysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, while systemic complement activation (the fluid phase) is similar between PD patients and patients with ESKD, higher intravascular complement depositions (solid phase) have been shown in children with PD compared to non-PD children with ESKD. Omental and parietal arterioles from PD patients demonstrated a higher presence of C1q, C3d, and C5b-9 ( 88 ).…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…Likewise, complement regulators were also shown to be downregulated in arterioles of PD patients. Furthermore, the C5b-9 deposition seen in the arterioles of PD patients correlated with the level of dialytic glucose exposure ( 88 ). However, this is probably not the only mechanism responsible for complement activation in PD patients.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…(F) CFB increased the ARG1 activity in BMDMs, resulting in the overproduction of polyamine. (6) and production of collagen (7), leading to progressive cardiac fibrosis (8). (9) nor-NOHA effectively inhibited the ARG1 activity in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular complications are most common in patients with chronic kidney diseases [7], and heart failure is the leading cause of mortality in patients with end-stage renal disease (ESRD) [8,9]; therefore, the role of complement system in the development of heart failure during ESRD is paid more and more attention by nephrologists. Aukrust et al reported that complement is related to heart failure for the first time, putting forward that complement components have potential as biomarkers of incident heart failure [10].…”
Section: Introductionmentioning
confidence: 99%